Threats to the stingless bees in the Brazilian Amazon: How to deal with scarce biological data and an increasing rate of destruction - Carvalho-Zilse, Gislene Almeida; Nunes-Silva, Carlos Gustavo (Bees: Biology, Threats and Colonies, 2012)
Deforestation and nest destruction by "professional" honey gatherers has drastically reduced the population of stingless bees in the Amazon, especially species of the Melipona genera, which are very good honey producers among the native stingless bees group. Here, we present some of the peculiar aspects of Melipona nesting biology, its ecology and its puzzling sex and caste determining system and show how these aspects are correlated with the rapidly growing rates of nest extinction by human activity. Conservation efforts are needed to promote more knowledge of the Melipona species and its biology as well as to enhance the beekeeping of stingless bees (Meliponiculture) in many communities and villages throughout the Brazilian Amazon in time to slow down nest destruction. We discuss issues and results from cryptic species as well as the logistical challenges of doing research in the Brazilian Amazon. Finally, we present suggestions for the development of appropriate and advanced technical training for beekeepers that can be used to strengthen and expand a rational way of exploiting the honey from stingless bees in the region. © 2012 Nova Science Publishers, Inc.